The Development of Learning Mobile Application of Latin-to-Balinese Script Transliteration - Indrawan, Gede; Pramarta, I Ketut (Jurnal Pekommas, 2019)
Balinese script writing allegedly towards extinction. The general objective of this research is to preserve this Balinese culture aspect through a technology approach. The specific objective is to develop learning mobile application of Latin-To-Balinese script transliteration, as one of the innovative technology products of the Universitas Pendidikan Ganesha – Bali, and to analyze crowd feedback of that application to know the user acceptance and to obtain feedback for future improvement. This android-based application can be used as a learning media at mandatory local content subject Balinese Language in elementary and secondary schools in Province Bali since so far, it could handle the transliteration complex behaviors based on document "The Balinese Alphabet" with about 98% accuracy level (148 right of 151 test case). The development of this application was based on Model-View-Controller design pattern and use dictionary data structure to hold special words. Crowd feedback data was obtained through Google Play Console in five months since the application release. There are more than 32 thousand installations and 152 ratings (63 ratings with reviews). Average rating score of 4.2 (from the maximum best score of 5) and positive general comments (57% from total review) reflects relatively good of the user acceptance to the application. Further improvement priority of the application based on top three feedback category, i.e. addition of: 1) copy-paste-share feature (18% of reviews total); 2) compatibility to the old version of android (5% of reviews total); and 3) character “ě” insertion feature for generating sign pepet of Aksara Bali (3% of reviews total).